Basilar impression complicating osteogenesis imperfecta type IV: the clinical and neuroradiological findings in four cases. Issue 3 (1st March 1999) - Hayes, M; Parker, G; Ell, J; Sillence, D
Abstract : OBJECTIVES: To describe the clinical and neuroradiological features of basilar impression in patients with osteogenesis imperfecta type IV. METHODS: Four patients with basilar impression were ascertained in a population study of osteogenesis imperfecta. All four had detailed clinical and neuroradiological examination with both CT and MRI of the craniocervical junction andposterior fossa structures. RESULTS: All four showed significant compression of the posterior fossa structures and surgical decompression was performed with relief of symptoms. CONCLUSION: Symptoms of cough headache and trigeminal neuralgia occurring in patients with osteogenesis imperfecta are indications for detailed clinical and neuroradiological investigation to document basilar impression.